The Effect of Adhatoda Vasica as A Herbal Supplement on The Performance, Nutrient Digestibility, and Blood Profile of Weaned Pigs - John, Alagbe Olujimi (International Journal of Applied and Scientific Research, 2024)
A 60-day trial was carried out to determine the impact of Adhatoda vasica as an herbal supplement on the performance, nutrient digestibility and blood profile of weaned pigs. 40 crossbred male pigs (Yorkshire × Landrace) with initial body weight of 10.21 ± 0.03 kg was distributed into 4 treatment consisting of 10 pigs each. On arrival, animals were quarantined for two weeks and fed basal diet which is adequate in all nutrients according to NRC (2012). Pigs in treatment 1 was fed basal diet without Adhatoda vasica leaf powder while those in treatment 2, 3 and 4 were fed same diet supplemented with Adhatoda vasica leaf powder at 200 g, 400 g and 600 g/kg respectively. A completely randomized design technique was adopted and the animals had unrestricted access to clean fresh water and feed. Quantification of phyto-constituents in Adhatoda vasica leaf powder showed that it contained higher concentration of flavonoids (102.1 mg/g) while steroids had the lowest concentration of 30.41 mg/g. Average daily weight gain was higher among pigs fed treatment 3 and 4, intermediate in treatment 2 and lowest in treatment 1. Average daily feed intake, feed conversion ratio and mortality were significantly (P<0.05) influenced by the treatment. Dry matter, ether extract, crude protein and crude fibre digestibility were influenced (P<0.05) by the treatment. Red blood cell, pack cell volume, mean platelet volume, mean corpuscular volume, mean corpuscular haemoglobin, white blood cell, total protein was significantly (P<0.05) different among the treatment except for aspartate amino transferase, alanine amino transferase and alkaline phosphatase (P>0.05). However, all values were within the established range for healthy pigs. In conclusion, Adhatoda vasica leaf powder can be supplemented in the diet of pigs without compromising their growth and health status.